Validación de constructo de la escala ESTE-R para medición de la soledad en la vejez en Bucaramanga, Colombia (2013)
There are many instruments that measure properties that are not observable, but are very important for understanding human behavior and work with it. Loneliness is a condition that affects all age groups, however, in old age there are conditions that may favor its occurrence and its consequences may be more feared and stronger than in other stages of life, becoming in a phenomenon of interest to be studied and intervened. ESTE-R scale is a useful tool for measuring loneliness, but must be validated to the context it is applied to obtain reliable results. For this reason was realized an Instrumental study, with a sample of 383 elder people residents in Bucaramanga, Colombia. Measurement was performed by Cronbach’s alpha and factor analysis, obtaining the following results: High reliability (0,925) for all scale variables and a solution of 4 factors that explain 58,6% of the data variance. Was concluded that the original structure of 4 factors is appropriate for Bucaramanga’s context and the proposal of 30 items presented here lets measure loneliness phenomenon.Keywords: loneliness, ESTE-R scale, old age, validity, reliability.